Multinational lessons from local and regional economic development agencies - Andrew Beer; Terry L. Clower; Alaric Maude; Graham Haughton (European Regional Science Association (ERSA), 2004)
This paper discusses the commonalities and differences in local and regional economic development (LRED) across England, Northern Ireland, Australia and the US. The focus is on four themes: the institutional characteristics of the respondents; governance, partners and partnerships; the objectives, regional capacity building and business service activities of responding agencies; and the self-assessment of effectiveness by LRED organisations. Our analysis is based on a survey of LRED agencies in the above-noted countries using a common questionnaire that was slightly adapted for each study area. Using logistic regression, we identify the practices and strategies of local and regional economic development agencies that are associated with higher levels of effectiveness. When all participating nations' LRED organisations are jointly evaluated, several practices emerge as being positively related to agency performance including being actively involved in industrial estates, labour training and recruitment, marketing the agency's region to international markets, and promoting industry clusters. Also showing as being positively related to performance are variables identifying whether or not the agency subsidized relocation costs for new businesses, helps local companies access venture capital, engages in education and training programs targeted at youths, and enhances networking opportunities for local business people. Interestingly, we found statistically significant negative relationships between agency effectiveness and engaging in tourism promotion activities, training minority groups, and conducting target industry studies, though this may reflect a correlation between certain activities and problematic economic environments. Though our research methodology of relying on self-assessed performance measures does not allow us to draw sweeping conclusions, we are confident that these findings provide a beginning for identifying a set of best practices that are appropriate for LRED organisations in a multinational setting.
Keywords: 330